The role of controlling shareholders in determining investments of intellectual capital among Taiwanese semiconductor companies - Hsieh, Chin-Hsien; Irene, Wei Kiong Ting; Asif, Jawad; Le, Hanh Thi My (Emerald Publishing Limited, 2019)
Purpose: Although intellectual capital (IC) has been proven to be value-added for companies, the drivers of IC performance remain an under-researched area. From the perspective of corporate governance, the purpose of this paper is to examine how controlling the ownership of shareholders would influence IC performance. Design/methodology/approach: This study utilized value-added intellectual capital (VAICTM) and its subcomponents, namely human capital, structural capital and capital employed efficiencies, to proxy for IC performance and regression analyses to assess the association between controlling the ownership of shareholders and the IC performance of Taiwanese listed semiconductor firms for the years 2009–2017. Findings: Results show that controlling the ownership of shareholders is nonlinearly related to IC performance. Specifically, controlling their ownership positively affects the level of IC performance up to an optimal point before it turns to be a negative relationship thereafter. Practical implications: The results of this study can help policy makers and other stakeholders understand the role of controlling shareholders in determining IC performance. The findings of this study suggest a nonlinear relationship between controlling the ownership of shareholders and IC. Originality/value: This study provides an extended perspective in studies related to the determinants of IC by considering the resources provided by controlling shareholders. The definitions of controlling interests and IC applied in this study are compared and aligned with those found in the International Financial Reporting Standard 10 – Consolidated Financial Statements and the International Integrated Reporting Council, respectively.